Questionando culturas e identidades, utopias e fatalidades: Reflexões de um sociólogo na solidão do quarto n.o 514 de um Meliá Confort - José Machado Pais (Revista Crítica de Ciências Sociais, 2002)
In the solitude of a room at a Meliá Confort Hotel, a frustrated sociologist struggles with an anxiety attack provoked by the responsibility of having to comment on two volumes of a voluminous work. Disappointed with the notes he has scribbled, he decides to redo the paper seeking inspiration in the hic et nunc of his discontent. Carried by a spontaneous curiosity, our sociologist starts from the contingencies and banalities of our quotidian in order to arrive at a world of meanings through mediations between the particular and the global, the individual and the collective, the subjective and the objective. The (lived) world that surrounds him seems to unveil itself in a specter of cultures and identities from the moment when it is sociologically problematized (conceived). Is it possible to unveil the social through the immediacies of the quotidian? Maybe it is, maybe it isn’t. All depends on whether the sociological questionings are capable or not of recapturing the world in its apparent facticity, which is given by the epidermal features of the quotidian.